Revealing Microplastic Contamination in Mangrove Sediments from Setiu Wetlands, Malaysia - Mohd Maulana, Nur Syafiqah; Zulkifli, Muhammad Shiddiq; Khalid, Aina Arifah; Shahrudin, Rohani; Tuan Anuar, Sabiqah; Jaafar, Maisarah; Ariffin, Effi Helmy (Universitas Gadjah Mada, 2025)
Mangrove ecosystems are vital for biodiversity conservation and coastal protection, serving as significant sinks for microplastics by trapping debris from both land and marine sources. This study investigates microplastic contamination in the mangrove sediments of Setiu Wetlands, Terengganu, a biodiversity hotspot with a unique landscape. Results revealed a concerning abundance of 2292 microplastic particles/kg of dry-weight sediment, with a high proportion of small-sized microplastics (< 1 mm). Areas influenced by aquacultural activities displayed the highest abundance, highlighting the connection between human activities and contamination levels. Over 80% of the microplastics were fibers, primarily transparent and black, with surface analysis revealing signs of environmental degradation, including cracks and pits. These surface modifications may facilitate biofilm growth and metal binding, potentially increasing their toxicity. Polypropylene was the most common polymer detected, linking contamination to the breakdown of packaging materials, fishing nets, and ropes. A significant inverse correlation was found between sediment pH and microplastic abundance, while no relationship was observed with organic matter content. These findings highlight the alarming presence of microplastics in mangrove ecosystems, stressing the need for urgent action in waste management, plastic reduction, and further investigation into the ecological consequences of this pervasive threat.